Writing wounds : the inscription of trauma in post-1968 French women's life-writing - Robson, Kathryn (Genus--gender in modern culture ;, 2004)
In the last decade, the question of how trauma is remembered and narrated has become increasingly crucial in literary studies and in psychotherapy. Writing Wounds rethinks the relation between trauma, memory and narrative through readings of key fictional, autobiographical and "autofictional" texts by recent French women writers: Marie Cardinal, Chantal Chawaf, Hélène Cixous, Charlotte Delbo, Béatrice de Jurquet and Sarah Kofman. By drawing on and also interrogating recent theories of trauma, this study shows that trauma is inscribed in writing through recurring images of the body and of bodily wounding that mark the limits and possibilities of narrativisation. This book has a double aim: to offer new readings of texts by modern French women writers and to rethink the crucial question of how narratives of trauma are to be read. Writing Wounds will be of interest to researchers working on trauma, modern French literature, women's writing or "life-writing" as well as to a range of undergraduate and postgraduate courses on trauma and narrative.